Sindroma Laurence-Moon-Bardet-Biedl - Ahmad Yusuf Aliridha, Ahmad Yusuf Aliridha (Universitas Gadjah Mada, 1985)
A 10-year old Javanese boy suffering from Laurence-Moon-Bardet-Biedl Syndrome characterized by retinitis pigmentosa, myopia, polydactily, obesity, hypogenitalism and mental retardation has been reported. Family history showed that one of his brothers had also the same abnormalities, while his two other brothers as well as his parents were perfectly normal. The possibility of the transmission of this disease was X -linked recessive. For this patient, a comprehensive management by ophthalmologists, paediatricians, psychiatrists and surgeons was necessary. Special education was needed to handle his mental retardation and his visual disturbances, and genetic counseling was necessary for the patient and his family. Key Words: Laurence-Moon-Bardet-Biedl Syndrome - X-linked recessive gene - genetic counseling - retinitis pigmentosa - myopia